2020
DOI: 10.1002/clc.23529
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of left atrial geometry in dilated cardiomyopathy patients: A cardiovascular magnetic resonance study

Abstract: Background Clinical significance of left atrial (LA) function and geometry in patients with dilated cardiomyopathy (DCM) remains uncertain. Hypothesis LA geometric parameters assessed by cardiac magnetic resonance (CMR) predict the prognosis in patients with DCM. Methods The present study included patients with DCM and sinus rhythm who underwent CMR between December 2007 and April 2018. LA volume was measured using CMR. LA sphericity index was computed as the ratio of the measured maximum LA volume by the volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The prognostic role of contractile function loss and LA dilatation has been demonstrated in a large cohort of patients with DCM (192) and recently confirmed with the use of CMR (193). LA maximal volume (LA max ) resulted to be effective in predicting the occurrence of a composite endpoint including death or heart transplantation in a population of 337 patients with DCM who were followed-up for a mean period of 41 ± 29 months.…”
Section: Dilated Cardiomyopathymentioning
confidence: 86%
“…The prognostic role of contractile function loss and LA dilatation has been demonstrated in a large cohort of patients with DCM (192) and recently confirmed with the use of CMR (193). LA maximal volume (LA max ) resulted to be effective in predicting the occurrence of a composite endpoint including death or heart transplantation in a population of 337 patients with DCM who were followed-up for a mean period of 41 ± 29 months.…”
Section: Dilated Cardiomyopathymentioning
confidence: 86%
“…First and foremost, studies that analyzed the role of echocardiography in LA remodelling, phasic function and geometry have begun to emerge. They had shown that LA phasic function parameters were strongly associated with HF, impaired LV relaxation and compliance, atrial fibrillation and AHT [ 10 , 20 , 31 , 32 , 33 ]. LA conduit function was found to be defective even before LV hypertrophy and enlargement occurred [ 34 ], and to be directly associated with diastolic dysfunction, its severity [ 32 ] and progression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LA sphericity index (LASI) is a novel marker that characterizes LA’s shape and remodelling which might play important roles in outcome prediction, but studies are just in their infancy [ 18 ]. LASI was able to predict the recurrence of atrial fibrillation [ 19 ] and HF hospitalization in NIDCM [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…LA sphericity index has been used as an independent predictor of hospitalization for heart failure in patients with dilated cardiomyopathy (64), but its correlation with atrial fibrillation is still not well understood (65). LA sphericity has been proposed as a potentially earlier and more sensitive indicator of atrial fibrillation-related atrial remodeling compared to traditional markers such as LA enlargement (63).…”
Section: Sphericity Indexmentioning
confidence: 99%